PERLAWANAN PIHAK KE TIGA (DERDEN VERZET) ATAS PUTUSAN BADAN ARBITRASE NASIONAL SYARIAH (BASYARNAS) - Muhammad Rutabuz Zaman (MIYAH : Jurnal Studi Islam, 2021)
This research article describes the resistance of a third party (Derden Verzet) to the decision of the sharia national arbitration body (BASYARNAS), where we know the form of Law of the Republic of Indonesia Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution Article 60 states that, final and have permanent legal force and bind the parties ". In his explanation, it is explained that, the arbitration award is a final decision and thus cannot be appealed, appealed or reviewed. " This research method uses a normative juridical approach and a conceptual approach, namely an approach based on statutory regulations (Statue Approach) and an approach by looking at the principles or legal principles that apply in statutory regulations. The results of this study state that the Law of the Republic of Indonesia Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, does not regulate the resistance of a third party (derden verzet) to the BASYARNAS Decision. For third parties who feel their rights and interests have been harmed by the BASYARNAS decision, they can file a challenge to the religious court which carries out the execution of the BASYARNAS verdict.Key Words: derden verzet, BASYARNAS, and Law of the Republic of Indonesia